APLIKASI BACARA DALAM BELAJAR MEMBACA PERMULAAN UNTUK ANAK DISLEKSIA - Hamida, Nazilatul; Marlina, Marlina; Iswari, Mega; Zulmiyetri, Zulmiyetri; Yuliana, Syari; Triswandari, Retno; Taufan, Johandri; Arnez, Gaby (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
For children with learning disabilities such as dyslexia, early reading skills often present a challenge that hinders literacy achievement. Difficulty recognizing letters and connecting sounds is a major obstacle in the learning process. Therefore, innovative, interactive, and adaptive learning media are needed to meet the child's specific needs. This research aims to develop the Bacara application as an interactive learning medium to improve early reading skills in children with dyslexia. The development process uses a Research and Development (R&D) approach with the ADDIE model, which includes the stages of Analysis, Design, Development, and Implementation. Evaluation is limited to the Implementation stage due to time and condition limitations. The Bacara application is designed using Articulate Storyline software, equipped with material features, interactive quizzes, audio guides, and the use of dyslexia-friendly fonts. Data collection techniques and tools through observation, interviews, tests, and validation tests by media experts, material experts, and language experts. The results of the study indicate that the Bacara application is declared feasible in terms of content and appearance, practical in use, and has the potential to be used as a supporting medium in developing early reading skills in dyslexic children. This media is suitable for widespread use and is recommended to be accompanied by training for educators so that its use can run optimally according to the needs of children.